Financial and economic aspects of food market security - Arych, Mykhailo (My University, 2021)
The main financial and economic factors and conditions for the security of the food market of the state are analyzed in the work, the principles of formation of the state policy in the field of food security, etc. are investigated. The development of market relations creates competitive conditions for doing business for all participants, which usually creates the call sign for improving the efficiency of doing business. The issue of food market security needs special attention here. У роботі проаналізовано основні фінансові та економічні аспекти та умови для безпеки продовольчого ринку держави, досліджено принципи формування державної політики у сфері продовольчої безпеки тощо. Розвиток ринкових відносин формує конкурентні умови ведення господарської діяльності для всіх учасників, що звичайно створює позивні умови для підвищення ефективності ведення бізнесу. Особливої уваги тут потребує питання безпеки продовольчого ринку.
Keywords: кафедра фінансів; efficiency; insurance; food market security; food industry; competitiveness of enterprise; страхування; безпека продовольчого ринку; харчова промисловість; конкурентоспроможність підприємства; ефективність